Repeated sprint swimming performance after low- or high-intensity active and passive recoveries - Toubekis, A. G.; Adam, G. V.; Douda, H. T.; Antoniou, P. D.; Douroundos, I. I.; Tokmakidis, S. P. (The Journal of Strength and Conditioning Research, 2011)
The purpose of this study was to examine the effects on sprint swimming performance after low- and high-intensity active recovery (AR) as compared to passive recovery. Ten male competitive swimmers (age: 17.9 ± 2.3 years; body mass: 73.2 ± 4.0 kg; height: 1.81 ± 0.04 m, 100-m best time: 54.90 ± 1.96 seconds) performed 8 × 25-m sprints with 120-second rest intervals followed by a 50-m sprint 6 minutes later. During the 120-second and the 6-minute interval periods swimmers rested passively (PAS) or swam at an intensity of 40% (ACT40; 36 ± 8% of the VO2max) and 60% (ACT60; 59 ± 7% of the VO2max) of their individual 100-m velocity. Performance time of the 8 × 25-m after ACT60 was slower compared with PAS and ACT40, but no difference was observed between ACT40 and PAS conditions (PAS: 12.15 ± 0.48, ACT40: 12.23 ± 0.54, ACT60: 12.35 ± 0.57 seconds, p < 0.05). Performance time of the 50-m sprint was no different between conditions (PAS: 26.45 ± 0.91; ACT40: 26.30 ± 1.18; ACT60: 26.21 ± 1.19 seconds; p > 0.05). Blood lactate concentration was not different between PAS, ACT40, and ACT60 after the 8 × 25-m and the 50-m sprints (p > 0.05). Passive recovery, or low intensity of AR (40% of the 100-m velocity), is advised to maintain repeated 25-m sprint swimming performance when a 2-minute interval period is provided. Active recovery at an intensity corresponding to 60% of the 100-m velocity decreases performance during the 25-m repeated sprints without affecting the performance time on a subsequent longer duration sprint (i.e., 50 m).